2019
DOI: 10.1002/anie.201901596
|View full text |Cite
|
Sign up to set email alerts
|

Selective and Efficient Removal of Fluoride from Water: In Situ Engineered Amyloid Fibril/ZrO2 Hybrid Membranes

Abstract: We report a new strategy for efficient removal of F− from contaminated water streams, and it relies on carbon hybrid membranes made of amyloid fibril/ZrO2 nanoparticles (<10 nm). These membranes exhibit superior selectivity for F− against various competitive ions, with a distribution coefficient (Kd) as high as 6820 mL g−1, exceeding commercial ion‐exchange resins (IRA‐900) by 180 times and outdoing the performance of most commercial carbon‐activated aluminum membranes. At both low and high (ca. 200 mg L−1) F−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 227 publications
(112 citation statements)
references
References 39 publications
7
105
0
Order By: Relevance
“…7b) could be tted to three peaks, namely, O 2À at 529.5 eV, OH À at 530.4 eV, and CO 3 2À at 531.4 eV. 16,45,46 Aer phosphate adsorption, the area ratio XPS spectra (Fig. 2b) of FCB/MAC before and aer adsorption were similar, indicating that the iron oxide did not participate in the adsorption process.…”
Section: Xps Analysismentioning
confidence: 91%
“…7b) could be tted to three peaks, namely, O 2À at 529.5 eV, OH À at 530.4 eV, and CO 3 2À at 531.4 eV. 16,45,46 Aer phosphate adsorption, the area ratio XPS spectra (Fig. 2b) of FCB/MAC before and aer adsorption were similar, indicating that the iron oxide did not participate in the adsorption process.…”
Section: Xps Analysismentioning
confidence: 91%
“…25,456,458 The concept has further been extended to remove halogen contaminants from water, such as in the case of fluoride, by first capturing transition metals on the fibrils, then growing them in situ into fine transition metal nanoparticles, which finally, by adhering to the amyloid surface, are capable of binding targeted fluoride contaminants. 459 The growth of metal ions on the surface of amyloids into metal nanoparticles conjugated to the amyloid fibrils can be further exploited for applications as diverse as heterogeneous catalysis 460 and human nutrition. For example, by growing iron oxide nanoparticles from Fe 2+ bound on the surface of b-lactoglobulin amyloid fibrils, Shen et al 24 showed that the resulting hybrids maintained iron at the right oxidation state (i.e., the II form, which is more bioavailable than the III form), which could then be used to target iron deficiency in vivo.…”
Section: Artificial Amyloids and Engineering Opportunitiesmentioning
confidence: 99%
“…In the past decade, various types of solid sorbents have been attempted for CCS. Examples include zeolites (Megías-Sayago et al, 2019), modified porous silicas (Dassanayake et al, 2017), metal organic frameworks (MOFs) (Shi et al, 2019), calcium looping sorbents (Zhu et al, 2017), polymer membranes (Ahmad et al, 2016;Zhang et al, 2019), and nanoporous carbons (NCs) . In particular, MOFs and NCs have received much attention due to their excellent capture performance.…”
Section: Introductionmentioning
confidence: 99%